Approximate entailment: Definition, types, causes, manifestations - Hassen, Ali AbdulHussein (Thi Qar Arts Journal, 2024)
This research aims to shed light on a neglected aspect of pragmatic theory and to emphasize an important part of conversational implicature, namely approximate entailment. This type of entailment has not received the attention and care it deserves. Therefore, this research introduces and explains its types, highlighting its importance. Ignoring its causes can lead to a breakdown in communication between the text producer and the receiver, causing problems and misunderstandings between the interlocutors, which may result in the loss of affection. As Gibran Khalil Gibran said, "Between what is said and not meant, and what is meant and not said, much love is lost." At the same time, this type of entailment can be used to avoid some embarrassing situations that a person may encounter in daily life. Real-life experiences have shown that it can be a means of salvation and change in a person’s circumstances. The researcher bases his analyses on real-life examples from rhetorical and literary books, examining the implied meaning in each linguistic incident. These examples serve as evidence and illustrations of this type of entailment. The researcher analyzes them and uncovers the underlying causes of the misunderstandings. The conclusion includes a set of results, recommendations, and suggestions that aim to reduce the occurrence of this type of entailment or enhance its positive effects when circumstances necessitate its use.